Variation in brain connectivity during motor imagery and motor execution in stroke patients based on electroencephalography - Guo, Dongju; Hu, Jinglu; Wang, Dezheng; Wang, Chongfeng; Yue, Shouwei; Xu, Fangzhou; Zhang, Yang (Frontiers in Neuroscience, 2024)
The objective of this study was to analyse the changes in connectivity between motor imagery (MI) and motor execution (ME) in the premotor area (PMA) and primary motor cortex (MA) of the brain, aiming to explore suitable forms of treatment and potential therapeutic targets.Methods: Twenty-three inpatients with stroke were selected, and 21 right-handed healthy individuals were recruited. EEG signal during hand MI and ME (synergy and isolated movements) was recorded.Correlations between functional brain areas during MI and ME were compared.Results: PMA and MA were significantly and positively correlated during hand MI in all participants.The power spectral density (PSD) values of PMA EEG signals were greater than those of MA during MI and ME in both groups. The functional connectivity correlation was higher in the stroke group than in healthy people during MI, especially during left-handed MI. During ME, functional connectivity correlation in the brain was more enhanced during synergy movements than during isolated movements. The regions with abnormal functional connectivity were in the 18 th lead of the left PMA area.Left-handed MI may be crucial in MI therapy, and the 18 th lead may serve as a target for non-invasive neuromodulation to promote further recovery of limb function in patients with stroke. This may provide support for the EEG theory of neuromodulation therapy for hemiplegic patients.